The use of an automatic defibrillator by non-sanitary personnel in sport areas: an Observational Study - Lupo, Roberto; Giordano, Giulia; Artioli, Giovanna; Calabrò, Antonino; Caldararo, Cosimo; Zacchino, Simone; Conte, Luana; Santoro, Pietro; Carriero, Maria Chiara; Carvello, Maicol (Acta Biomedica Atenei Parmensis, 2020)
Introduction: In industrialized countries, sudden cardiac death is a serious public health problem that accounts for about 15% to 20% of all deaths, with an incidence of 0.5 to 3 deaths per 100,000 athletes. In recent years, although both first aid prevention programs and the availability of External Automatic Defibrillator (AED) in public places have increased, few data are available with respect to real knowledge about the use of such devices. The aim of this study is to detect the level of knowledge and skills in the use of automatic external defibrillators among sports and management staff in sports facilities. Materials and Methods: A cross-sectional, multicentre study conducted in 16 sports facilities in the Province of Lecce, Italy, and targeted to all the athletic and managerial staff of these sports facilities. Information was obtained through a validated questionnaire consisting of 27 items. Results: 339 participants of which 59.3% male (n=201) (average=33.6; SD=13.1). 51.6% (n=175) were informed about the presence of the defibrillator, only 38.1% (n=129) declared to know where it was placed and 43.7% (n=96) considered it to be quite or very accessible. The majority of them (78.8%; n=267) were never involved in a training course and declared limited knowledge about the use of this device. Conclusions: Respondents stated that they have poor knowledge and skills in the use of the defibrillator, its operation and maintenance, which could reduce the positive outcomes of early treatment. Further studies should be conducted, although it may be appropriate to implement specific training courses for personnel working in sports centres.